The efficacy of bisphosphonates for osteoporosis in young Cushing’s disease patients with biochemical remission: a retrospective cohort study - Sun, Quanya; Sun, Wanwan; Ye, Hongying; Zhang, Shuo (Frontiers in Endocrinology, 2024)
Background：Patients with Cushing's disease (CD) often experience slow recovery of bone mineral density (BMD), and the effectiveness of anti-osteoporosis drugs in young CD patients who have achieved biochemical remission after surgery is not well understood.. Therefore, we aimed to explore whether bisphosphonates could help accelerate the recovery of osteoporosis in young CD patients with remission. Methods: We retrospectively enrolled 34 young patients with CD who achieved postoperative biochemical remission. All patients suffered from osteoporosis before surgery and were divided into postoperative bisphosphonate treatment group (16 cases) and without bisphosphonate treatment group (18 cases). Clinical data, BMD (Z Value), and bone turnover markers were collected at the time of diagnosis and one year after successful tumor resection. Results: The Z values in the lumbar spine showed slight improvement in both groups at follow-up compared to baseline, but this improvement was not statistically significant. There was no significant difference observed between the two groups at follow-up. One year after operation, bone formation markers (OC and P1NP) were significantly higher than those at baseline in both groups. However, OC and P1NP in the bisphosphonate treatment group were lower than those in control group at one year follow-up. In without bisphosphonate treatment group, β-CTX from follow-up visit was higher than that at baseline, while no significant difference was observed in the bisphosphonate treatment group before and after surgery. Conclusion: Young patients with Cushing's disease combined with osteoporosis might not benefit from bisphosphonate therapy for osteoporosis recovery in the first year after achieving biochemical remission.